PROSTHETIC TREATMENT OF PATIENT WITH TOTAL HARD PALATE RESECTION - Ivan Gerdzhikov (Peytchinski Publishing, 2019)
Introduction: Operative treatment of tumours of the maxilla impairs the barrier between the oral and nasal cavities, making difficult or impossible to eat, speak, and drink liquids. Aim: The purpose of the clinical case described, is to examine the possibility of prosthetic treatment in patients with fully resected hard palate, the treatment effect and recovery of impaired functions. Materials and methods: The article presents the prosthetic treatment of a patient with resection of the entire hard palate as a result of an oncological disease. Due to complete edentulism, the treatment plan included the construction of an obturator and a complete lower denture. Functional impressions with additive silicone were taken with custom trays of the light-cured acrylic resin after pre-edging with wax impression material (ISO Functional GS). The dentures were made of a colourless heat cured the acrylic resin. The volume and localization of the defect necessitated a specific shaping of the replacement part of the obturator. In order to provide the necessary retention and stability, we used our own modification of the open cup-shaped form in which the edges of the replacement part were extended distally in the area of the soft palate. Results: The results of the treatment showed good retention and stability of the obturator and the lower denture. The feeding, speech and swallowing of the patient were successfully restored. Conclusion: Prosthetic treatment with a definitive obturator allows optimal sealing of the maxillary defect even with a fully removed hard palate.